Tailoring second-line or above therapy for patients with advanced or metastatic gastric cancer: A multicenter real-world study - Nie, Caiyun; Xu, Weifeng; Lv, Huifang; Gao, Xiaohui; Li, Guofeng; Chen, Beibei; Wang, Jianzheng; Liu, Yingjun; Zhao, Jing; He, Yunduan; Wang, Saiqi; Chen, Xiaobing (Frontiers in Pharmacology, 2022)
Background: There is currently still a lack of effective therapeutic manner after the failure of first-line therapy for patients with advanced or metastatic gastric cancer. The present study aimed to evaluate the clinical efficacy and safety of different treatment strategies as second-line or above therapy for patients with advanced or metastatic gastric cancer. Methods: This was an observational multicenter real-world study. From January 2018 to December 2020, advanced or metastatic gastric cancer patients who have failed prior therapy were enrolled and treated with chemotherapy, anti-angiogenic TKIs (tyrosine kinase inhibitors) + chemotherapy or TKIs + ICIs (immune checkpoint inhibitors). In this study, progression free survival (PFS) was the primary end-point. Other evaluation indicators were objective response rate (ORR), disease control rate (DCR), overall survival (OS) and drug toxicities. Results: 162 patients were enrolled, of which 61 patients received chemotherapy, 47 patients received TKIs plus chemotherapy, and 54 patients received TKIs + ICIs. No statistically significant difference existed in ORR among groups (16.4% vs. 19.1% vs. 18.5%, p = 0.924). Patients who received TKIs plus chemotherapy obtained better DCR compared with the chemotherapy group (78.7% vs. 54.1%, p = 0.008), and simultaneously, the median PFS (3.3 m vs. 2.8 m, p = 0.001) and OS (8.0 m vs. 5.8 m, p = 0.005) in TKIs plus chemotherapy group were superior to chemotherapy group. Consistent results were observed in subgroup analysis, including sex, age, ECOG, number of metastatic sites and treatment line. No statistically differences were found between TKIs + ICIs and the chemotherapy group concerning DCR (63.0% vs. 54.1%, p = 0.336), median PFS (3.0 m vs. 2.8 m, p = 0.051) and OS (5.2 m vs. 5.8 m, p = 0.260). Different treatment manner present a special spectrum of adverse events (AEs), and the incidence of Grade 3–4 AEs were 31.1%, 38.3% and 18.5%, respectively. Conclusion: Compared with chemotherapy, anti-angiogenic TKIs plus chemotherapy demonstrated superior second-line or above therapeutic efficacy for advanced or metastatic gastric cancer with well tolerated toxicity. However, TKIs + ICIs failed to demonstrate a clinical advantage over chemotherapy.